Evaluation of T-cell responses to novel RD1- and RD2-encoded Mycobacterium tuberculosis gene products for specific detection of human tuberculosis infection - Liu, Xiao-Qing; Dosanjh, Davinder; Varia, Hansa; Ewer, Katie; Cockle, Paul; Pasvol, Geoffrey; Lalvani, Ajit (Infection and immunity, 2004)
The tuberculin skin test for diagnosing Mycobacterium tuberculosis infection suffers from antigenic cross-reactivity of purified protein derivative with BCG, resulting in poor specificity in BCG-vaccinated populations. Comparative genomics has identified several genetic regions in M. tuberculosis and M. bovis that are deleted in M. bovis BCG. Proteins encoded in these regions will form the basis of new specific T-cell-based blood tests that do not cross-react with BCG, but only two, early secretory antigen target 6 and culture filtrate protein 10, have been studied in detail in humans. We investigated four novel gene products, encoded by RD2 (Rv1989c) and RD1 (Rv3873, Rv3878, and Rv3879c), that are absent from most or all of the vaccine strains of BCG, respectively. Sixty-seven overlapping peptides were tested in ex vivo gamma interferon enzyme-linked immunospot assays in 49 patients with culture-confirmed tuberculosis and 38 healthy BCG-vaccinated donors. Forty-five percent (95% confidence interval [CI], 31 to 57%) and 53% (95% CI, 39 to 67%) of the tuberculosis patients responded to Rv3879c and Rv3873, respectively, identifying these proteins as major M. tuberculosis T-cell antigens in humans, while 35 and 25% of the patients responded to Rv3878 and Rv1989c, respectively. Of the 38 BCG-vaccinated donors, 1 (2.6%) responded to peptides from Rv3878 and Rv3879c, 3 (7.9%) responded to Rv3873, and none responded to Rv1989c. Exclusion of cross-reactive peptides encoded in conserved motifs of Rv3873, a PPE family member, increased its specificity to 97.4%. The high specificity of Rv3879c peptides and nonconserved Rv3873 sequences, together with their moderate sensitivity in tuberculosis patients, identifies these peptides as candidates for inclusion in new T-cell-based tests for M. tuberculosis infection.